All-in-one three-phase smart meter and power quality analyzer with extended IoT capabilities. (January 2023) - Viciana, Eduardo; Arrabal-Campos, Francisco M.; Alcayde, Alfredo; Baños, Raul; Montoya, Francisco G.
Abstract: The traditional power grid is evolving into a new smart grid that requires better coordination of supply and demand, making it necessary to establish precise monitoring strategies in order to determine grid status in real-time. With the aim of providing a low-cost device based on open-hardware and open-source software to the technicians, engineers, and scientists around the world, this paper presents the three-phase openZmeter (3Ph-oZm), an all-in-one device that allows measuring and computing electrical data related to energy and power quality features in three-phase power networks. It has been designed to perform advanced computations for voltage, current, frequency, power, and energy. 3Ph-oZm is able to process high order harmonics, and log power quality disturbance events defined according to the recommendations of some international standards organizations. The data and its associated features are processed on-site using custom software specifically designed and programmed for this purpose that relies on advanced signal analysis techniques. This smart meter significantly improves the capabilities of the single-phase version, and overcomes certain shortcomings of other commercial devices, both in terms of versatility and data acquisition and processing capabilities. The system has been calibrated and validated using laboratory testing set-up and real-world applications, such as long-term photovoltaic power plant metering. The capabilities of 3Ph-oZm can also support a variety of other electrical applications, such as three-phase induction motor health monitoring, energy savings, or microgrid state estimation. Highlights: A new three-phase open-source smart meter and power quality analyzer is designed and built. Several international standards like IEC 61000-4-30 or EN50160 are implemented to conform a class B metering device. The system has been calibrated and tested in laboratory and real scenarios like a PV power plant.